Biocontrol of Listeria monocytogenes in fish by enterocin AS-48 and Listeria lytic bacteriophage P100. (March 2016) - Baños, Alberto; García-López, José David; Núñez, Cristina; Martínez-Bueno, Manuel; Maqueda, Mercedes; Valdivia, Eva
Abstract: The purpose of this study was to determine the ability of enterocin AS-48 to control Listeria monocytogenes in fish during storage at 4 °C. AS-48 (0.37 μg/cm 2 ) was tested singly and in combination with phage P100 (2.3 × 10 7  PFU/cm 2 ) on a cocktail of 10 3  CFU/cm 2   L. monocytogenes strains inoculated in fillet tissues of raw hake and salmon and in smoked salmon. In raw fish, AS-48 alone reduced listeria with respect to the untreated control by 1.68, 2.79, 2.9, and 3.13 log CFU/cm 2 (in hake) and by 1.9, 2.55, 2.8, and 2.8 (in salmon) at 1, 2, 3, and 7 d, respectively. Phage P100 treatment also yields significant reductions (but lower than AS-48) in listeria counts in both raw fishes. A combined treatment of AS-48/P100 eliminated listeria from hake and salmon fillets from 2 and 1 days respectively. In smoked salmon, AS-48 reduced listeria by 2, 3.4, 4.5, 4.25, and 4.25 log CFU/cm 2 with respect to the control at 1, 5, 10, 15, and 30 d, respectively. P100 treatment also reduced listeria counts but in lesser quantities than AS-48. A combined treatment of AS-48/P100 reduced listeria below detection levels from 1 to 15 d; afterwards, a slight listeria reactivation was detected. Highlights: Enterocin AS-48 tested against Listeria monocytogenes in raw and smoked fish. AS-48 alone greatly reduces listeria counts in raw hake and salmon and smoked salmon. Phage P100 reduces listeria counts in raw hake and salmon and smoked fish. Combined AS-48/phage P100 treatment eliminates Listeria in raw hake and salmon. Recovery of AS-48 from fish food matrix gradually declined during storage.